Mother’s Knowledge with Self Efficacy in Handling Diarrhea for Toddlers - Intan Fazrin; Asifah Sholafiyah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Diarrhea is an endemic disease that has a potential to cause outbreak as a contributor to mortality in Indonesia, especially in children under five, so it must be dealt immediately. Mothers are essential figures in every monitoring of children’s health, especially in knowledge and self-efficacy in handling diarrhea.This research aims to analyze the relationship between mother’s knowledge and self-efficacy in handling diarrhea for toddlers at Garum Health Center. Researcher uses a quantitative design with cross sectional approach. The population of this study were all mothers whose toddler had diarrhea and came for treatment at the Garum Health Center Blitar. There are 35 respondents as the sample with accidental sampling technique. Researcher conducted informed consent first and then distribute the questionnaire about knowledge and self-efficacy. The data results were analysed by using the Spearman Rho. The respondents having sufficient knowledge as many as 15 respondents (42,9%), most of the respondents have high self-efficacy as many as 20 respondents (57,1%).The results of the Spearman Rank statistical test obtained the value of sig. 0.015 < 0.05 which indicates there is a relationship between mother's knowledge and self-efficacy in handling diarrhea in toddlers.Mothers who are able to do first aid on diarrhea in their toddlers properly and appropriately can be a factor in the toddler's recovery without referring their toddler to the health center. The good knowledge of mother must be followed by high self-efficacy that is able to carry out proper handling of toddlers with diarrhea.